Panggilan Hati, Tugas Profesi, Ataukah Kebanggaan Diri: Job Involvement pada Perawat - Wibowo, Danan Satriyo (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2024)
The profession of a nurse in recent times has been in the spotlight, apart from carrying out the role as medical personnel by the professional oath to provide health services, work involvement is the level at which a nurse is identified psychologically and the extent to which a nurse's performance affects his or her self-esteem as a form of job involvement. The research aims to map and determine the job involvement of nurses in carrying out their responsibilities as medical personnel in providing health services to patients. This research uses a descriptive quantitative method approach with survey techniques (cross-sectional survey design). The data collection technique uses a measurement job involvement scale adapted from Lodahl and Kejner. The sample in this study was 112 nurses who were determined randomly (simple random sampling). The results of the study showed that 73 nurses (65.2%) put a more professional attitude in carrying out their professional role as nurses in showing behavior of psychological involvement in work, there were 39 nurses (34.8%) who showed the work behavior of providing nursing care as a form of calling ( humanity).